Longitudinal Associations between Callous-unemotional (CU) Traits and School-based Affiliative Relationships among South Korean Children. Issue 4 (4th July 2022) - Hwang, Suhlim; Waller, Rebecca; Hawes, David J.; Allen, Jennifer L.
ABSTRACT: Objective: Callous-unemotional traits (CU) traits are characterized by low empathy, guilt, and reduced sensitivity to others' feelings, along with a reduced drive for social affiliation. However, little is known about the relationships between CU traits and social affiliation in the school context, or the influence of gender on these associations. This study tested reciprocal associations between CU traits and school-based affiliative relationships and explored gender as a potential moderator. Method: The sample included South Korean children aged 10 to 12 years (N = 218, M = 11.03, SD = .65, 52% boys). Children reported on CU traits, antisocial behavior, teacher-student relationship quality, and peer affiliation. Three-wave longitudinal cross-lagged models tested reciprocal associations between CU traits and affiliation with both teachers and peers, with multi-group modeling employed to test the moderating effect of gender. Results: Higher CU traits at time 1 predicted decreases in teacher affiliation at time 2 controlling for CU traits, teacher-child affiliation, and antisocial behavior at time 1, while lower teacher-child affiliation at time 2 predicted increases in CU traits at time 3 accounting for CU traits, teacher-child affiliation, and antisocial behavior at time 2. However, there were no reciprocal associations between CU traits and teacher affiliation nor significant associations between CU traits and peer affiliation. Gender did not moderate any pathways between CU traits and teacher or peer affiliation. Conclusions: Findings indicate CU traits may reduce teacher-child affiliation, potentially escalating risk for further increases in CU traits. Thus, teacher-child affiliation may represent an important target for school-based intervention for children with elevated CU traits regardless of gender.